TINJAUAN KINERJA DAN RESPONS PASAR TERHADAP SAHAM PT JAPFA COMFEED INDONESIA TBK DI BURSA EFEK INDONESIA - Dinda Widya Kumala; Eki Indriyanti; Avier Syarif Ananta Syahbana; Danendra Bramantyo; Suparta, I Made Suparta (Nirta Learning Centre, 2025)
This study aims to review the financial performance and market response toward the stock of PT Japfa Comfeed Indonesia Tbk (JPFA), which is listed on the Indonesia Stock Exchange. A descriptive qualitative approach was used, employing secondary data such as financial statements, historical stock price movements, and academic references related to the agribusiness industry. The findings indicate that JPFA recorded significant increases in revenue and net income in 2024, driven by operational efficiency and effective cost control strategies. A healthy capital structure, strong liquidity, and positive operating cash flows further reinforce the company’s financial stability. From a market perspective, investor response is reflected in the growth of earnings per share (EPS) and dividends, making JPFA stock fundamentally attractive. Therefore, JPFA shares are considered to have promising investment prospects in the medium to long term.